Probiotics, prebiotics, and organic acids as alternative to antibiotics and zinc oxide in diets for weaned piglets - Valente Júnior, Dante Teixeira (2024)
Two experiments were carried out with weaned piglets. In experiment I, the study aimed to evaluate the effects of dietary Bacillus subtilis DSM 32540 supplementation with or without different fiber sources for piglets. A total of 150 piglets (7.20 ± 0.98 kg) weaned at 21 days old were assigned to one of five treatments in a randomized block design, with ten replicates and three piglets per pen. Treatments consisted of negative control (NC, without ZnO and amoxicillin), positive control (PC, with ZnO and amoxicillin), NC + 0.5 g/kg of probiotic (PRO), NC + 0.5 g/kg probiotic + 5 g/kg cellulose as IDF + 5 g/kg inulin as SDF (PROCI), and NC + 0.5 g/kg probiotic + 50 g/kg wheat bran (PROWB). From D0 to D14 and D0 to D28, piglets fed NC or PROWB had the lowest (P < 0.01) average daily gain (ADG) and final body weight (BW), while piglets fed PRO and PROCI had similar ADG and BW to those fed PC. From D0 to D14, piglets fed PRO and PC had lower (P < 0.01) feed conversion ratio (FCR) than those fed NC. From D0 to D28, piglets fed PROWB and NC had the highest (P < 0.01) FCR, while there was no difference in FCR among PC, PRO and PROCI groups. Piglets fed PRO, PROCI and PROWB had lower (P < 0.001) diarrhea incidence than those fed NC. Piglets fed PC, PRO and PROCI and those fed PRO and PROWB had higher (P < 0.01) duodenum and jejunum villus heights (VH) and villus to crypt ratios, respectively, than those fed NC. Piglets fed NC had the highest (P = 0.045) serum DAO content, and no difference was observed among groups PC, PRO, PROCI and PROWB on serum concentration of DAO. In conclusion, B. subtilis DSM 32540 supplementation improves performance of piglets fed diets with or without pure fiber sources. In addition, regardless of the fiber source, B. subtilis DSM 32540 reduces diarrhea incidence and improves intestinal morphology and integrity of nursery piglets. In experiment II, the study investigated the effects of feed additive (FA) containing symbiotic and organic acids on performance and intestinal health of weaned piglets. A total of 288 piglets (BW = 6,53 ± 1,04 kg) were assigned to one of four treatments in a randomized block design, with nine replicates and eight piglets per pen. The treatments were NC (without ZnO), PC (with ZnO), FA1 (NC+1.0 kg/ton FA), and FA2 (NC+2.0 kg/ton FA). Piglets fed FA2 had the lowest (P = 0.01) gain:feed (G:F) between 21 and 35 days, while piglets fed FA1 and NC had similar G:F to those fed PC. Piglets fed NC hadthe lowest (P = 0.04) BW at 35 and 70 days, and those fed FA2 and NC had similar BW compared to PC group. Piglets fed NC had the highest (P = 0.03) fecal score, while no significant difference was observed among groups PC, FA1, and FA2. Piglets fed NC had the lowest (P = 0.03) jejunal VH, whereas VH of piglets fed FA1 and FA2 were comparable to those fed PC. Piglets fed FA1 had higher (P = 0.03) occludin expression compared to those fed NC, while piglets fed PC and FA1 had higher (P < 0.01) TGF-β1 expression compared to piglets fed FA2. In conclusion, although there were no discernible performance benefits, inclusion of 1.0 kg/ton of FA to diet without ZnO helps maintain gut health of piglets by improving intestinal morphology and epithelial integrity and stimulating immune system inactivation. Keywords: Immune system. Intestinal morphology. Piglets. Prebiotic. Symbiotic. Weaning.